Pengaruh Naungan Lentera, Alpukat, dan Sengon Terhadap Kondisi Iklim Mikro Pada Lahan Agroforestri Kopi Robusta - Islakhul Anam, Muhammad; Maghfiroh, Canggih Nailil; Puspaningrum, Yessita; Nasirudin, Mohamad; Faizah, Mazidatul (AGROSAINTIFIKA, 2023)
One of the factors that affect the growth and productivity of coffee plants is largely caused by microclimates such as air temperature, air humidity, wind speed and light intensity related to the type of shade used. The purpose of this study is to determine the effect of the use of shade on the growth and productivity of robusta coffee plants. This observation was carried out on the agroforestry coffee plantation land of Wonosalam District. The coffee plants observed were 5 to 7 years old, and the shade used in the observations were lamtoro trees, avocados and sengon trees. While the research design used was a randomized experimental design consisting of control shade and plant shade. Thus, based on the results of observations that have been made for one month, the highest results in the first week were obtained 25.5-26.30C at air temperature. While the highest observed humidity occurs in the first week and fourth week by 71%. The highest wind speed occurs in the third and fourth weeks of 4.8-5.0 km / hour. The highest light intensity produced occurred in the third week of the control shade, which was 37020 LUX. The results of these observations prove that the use of shade plants has no real effect on the production and growth of robusta coffee plants.